Discovery and Development of Kelch-like ECH-Associated Protein 1. Nuclear Factor Erythroid 2‑Related Factor 2 (KEAP1:NRF2) Protein–Protein Interaction Inhibitors: Achievements, Challenges, and Future Directions - Jiang, Zheng-Yu; Lu, Meng-Chen; You, Qi-Dong (Journal of medicinal chemistry, 2016)
The transcription factor Nrf2 is the primary regulator of the cellular defense system, and enhancing Nrf2 activity has potential usages in various diseases, especially chronic age-related and inflammatory diseases. Recently, directly targeting Keap1–Nrf2 protein–protein interaction (PPI) has been an emerging strategy to selectively and effectively activate Nrf2. This Perspective summarizes the progress in the discovery and development of Keap1–Nrf2 PPI inhibitors, including the Keap1–Nrf2 regulatory mechanisms, biochemical techniques for inhibitor identification, and approaches for identifying peptide and small-molecule inhibitors, as well as discusses privileged structures and future directions for further development of Keap1–Nrf2 PPI inhibitors.